Les forêts périurbaines franciliennes, des marges ? - Alexandra Monot (Bulletin de l’Association de Géographes Français)
In the Ile-de-France area, suburban forests still exist, but their size, uses and exploitations are different compared to other French forests. These suburban forests can in many respects be described as margins. First, they constitute “natural” spaces in an urban area. Moreover, they have a social, ecological and recreational role. The activities they are the site of are only marginal in the French productive system: forestry, hunting, mushroom picking. However the level of marginality increases from Paris to the periphery and from forest edges to forest interior.